Bridging Education To Innovation Through Entrepreneurial Orientation and Self-Efficacy: A Self-Determination Theory Perspective - Suparno, Antoni; Radianto, Wirawan Endro Dwi; Dewi, Liliana (Indonesian Journal of Business and Entrepreneurship, 2026)
Background: Entrepreneurial education (EE) has become a central topic in emerging economies; however, its interaction with entrepreneurial orientation (EO), entrepreneurial self-efficacy (ESE), and innovation capability (IC) remains underexplored, particularly in the Indonesian context. By positioning EO as a mediator and ESE as both a direct and moderating factor, this study extends prior research and provides a more integrative understanding of entrepreneurial behavior. Purpose: This study analyzes the role of entrepreneurial education in enhancing innovation capability by analyzing entrepreneurial orientation as a mediator and entrepreneurial self-efficacy as a moderator within the framework of Self-Determination Theory. Design/methodology/approach: The study employs a survey-based design with 166 valid responses analyzed using PLS-SEM, which allows testing of complex mediating and moderating effects simultaneously Findings/Result: The findings reveal that entrepreneurial education significantly boosts both entrepreneurial orientation and innovation capability. Entrepreneurial orientation mediates the impact of education on innovation by encouraging proactive, innovative, and risk-taking behaviors. As evidenced by the analysis, entrepreneurial self-efficacy demonstrated a substantial and direct impact on both the orientation towards entrepreneurship and the ability to innovate but did not show significant moderating effects. Conclusion: This study contributes theoretically by extending SDT through the integration of EO and ESE into the EE–IC relationship while empirically demonstrating the strong predictive power of the proposed model. From a practical perspective, the results suggest the importance of embedding EO-building experiences and ESE-enhancing interventions in entrepreneurship education, supported by policies that foster innovation ecosystems. Future research could expand this framework across different cultural and industrial settings. Originality/value (State of the art): This study offers a novel integrated model connecting educational, psychological, and behavioral constructs, contributing to the existing literature by addressing gaps in previous research and offering practical insights for entrepreneurship education in emerging markets. Keywords: entrepreneurial education, entrepreneurial orientation, innovation capability, entrepreneurial self efficacy, entrepreneur by design